Impact of digital intervention on activity behavior Neural network based analysis - Xiao, Yuling (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Background: The importance of physical activity has been recognized widely by both individuals and society. Together with changes brought by digitalization to our lives, wearable devices’ positive influence to users’ physical activity has attracted strong attention worldwide. Objective: The aim of the paper is to understand how digitalization affects people’s daily habits and health, and to study how digital intervention impacts on female and male’s physical activity habits during 10 weeks trail. Methods: A set of 10 weeks’ data was collected through white-collar workers who wore Polar Activity electronic monitors in their wrists. The study visualized the data patterns of their daily PA, steps, calories and sleep of the 10 weeks with Viscovery SOMine software, which is data visualization technique based on unsupervised data self-organizing. Results: At the end of the study period, the test group reported slightly increase of their physical activity over baseline than the control group. The average increase (over the control group) is 3%. Female test group’s physical activity has increased by 7% compared with female control group, while male test group has dropped by 1.4% than male control group. The major cluster’s increase over the control group for female and male are 20% and 50%. Conclusions: The intervention of wearable devices used to monitor activity with display and diary functions will positively increase users’ physical activity in average. Besides, major cluster among male and female get stronger positive increase of PA through the intervention of wearable devices than average. Lastly, women are more positively influenced by the intervention of wearable devices.